Treatment of destructive periodontitis with combined root resorption. Clinical case - V. V. Glinkin; Yu. A. Generalova; Y. A. Bakaev; F. V. Badalov; E. T. Demurova; I. A. Gorbatenko; Anna A. Litvinenko (LLC "Endo Press", 2022)
Pathological resorption is diagnosed quite often in the treatment of periodontitis and is considered a prognostic adverse symptom. Increasing the effectiveness of the therapeutic treatment of destructive periodontitis is associated with the development of methods of instrumental and drug effects on root canals and depends on the correct selection of endo-sealant to achieve the predicted result. The combined pathology of root resorption is no exception in the case of a correctly chosen treatment strategy. The article reports on the successful therapeutic treatment of a tooth with destructive periodontitis and combined root resorption. Radiographically proven that there is a complete recovery of periapical tissues. Long-term results indicate the effectiveness of the treatment.